Efficient resistance to grass carp reovirus infection in JAM-A knockout cells using CRISPR/Cas9. Issue 76 (May 2018) - Ma, Jie; Fan, Yuding; Zhou, Yong; Liu, Wenzhi; Jiang, Nan; Zhang, Jieming; Zeng, Lingbing
Abstract: The hemorrhagic disease of grass carp ( Ctenopharyngodon idellus ) induced by grass carp reovirus (GCRV) leads to huge economic losses in China and currently, there are no effective methods available for prevention and treatment. The various GCRV genotypes may be one of the major obstacles in the pursuit of an effective antiviral treatment. In this study, we exploited CRISPR/Cas9 gene editing to specifically knockout the DNA sequence of the grass carp Junctional Adhesion Molecule-A (gcJAM-A) and evaluated in vitro resistance against various GCRV genotypes. Our results show that CRISPR/Cas9 effectively knocked out gcJAM-A and reduced GCRV infection for two different genotypes in permissive grass carp kidney cells (CIK), as evidenced by suppressed cytopathic effect (CPE) and GCRV progeny production in infected cells. In addition, with ectopic expression of gcJAM-A in cells, non-permissive cells derived from Chinese giant salamander ( Andrias davidianus ) muscle (GSM) could be highly infected by both GCRV-JX0901 and Hubei grass carp disease reovirus (HGDRV) strains that have different genotypes. Taken together, the results demonstrate that gcJAM-A is necessary for GCRV infection, implying a potential approach for viral control in aquaculture. Highlights: gcJAM-A is necessary for GCRV infection. The antiviral activity of CRISPR/Cas9 to target gcJAM-A efficiently suppress multiple-genotypes GCRV infection. With ectopic expression of gcJAM-A in cells, the non-permissive cells could be highly infected by GCRV. The first application of CRISPR/Cas9 system to suppress viral infections in aquatic animals.